Wide-band hybrid amplifier operating in S-band region - Emami, Siamak Dawazdah; Hajireza, Parsin; Abd-Rahman, Faidz; Abdul-Rashid, Hairul Azhar; Ahmad, Harith; Harun, Sulaiman Wadi (Electromagnetics Academy, 2010)
Wide-band hybrid amplifier is theoretically proposed using a series configuration of Thulium-doped fiber amplifier (TDFA) and fiber Raman amplifier (FRA), which using the similar type of pump laser. The operating wavelength of this amplifier covers the bandwidth of entire short wavelength band (S-band) region by combining the gain spectrum of TDFA and FRA. The theoretical gain varies from 20 to 24dB within a wavelength region from 1460 to 1525nm and which is in a good agreement with the experimental result. The development of reliable high-power diode lasers in the 1420nm wavelength range will make this type of wide-band hybrid amplifier an interesting candidate for S-band optical telecommunication systems.